2014
DOI: 10.1007/s10964-014-0244-2
|View full text |Cite
|
Sign up to set email alerts
|

Daily Diary Reports of Social Connection, Objective Sleep, and the Cortisol Awakening Response During Adolescents’ First Year of College

Abstract: Poor sleep and alterations in the stress-sensitive hypothalamic-pituitary-adrenal (HPA) axis may be mechanisms through which loneliness impacts adolescents' well-being. Few researchers have explored whether daily variation in experiences of social connection predict day-to-day variation in sleep and HPA axis activity among adolescents navigating the college context. Using daily diary reports of social connection, objective measures of sleep (actigraphy), and naturalistic salivary assessment, the present study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
42
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 108 publications
3
42
1
1
Order By: Relevance
“…These findings have been confirmed with daily dairy data, wherein daily assessments of loneliness were prospectively associated with larger cortisol responses to awakening in adults and late adolescents (i.e. cortisol awakening response, or CAR, Adam et al, 2006; Doane and Adam, 2010, but see Sladek and Doane, 2015), while trait loneliness was associated with a flatter decline in diurnal cortisol in late adolescence (Doane and Adam, 2010, but see, Sladek and Doane, 2015), for a null association between trait loneliness and cortisol slope in the same age group). Despite the insights provided by those data, critical gaps remain unaddressed in this literature.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…These findings have been confirmed with daily dairy data, wherein daily assessments of loneliness were prospectively associated with larger cortisol responses to awakening in adults and late adolescents (i.e. cortisol awakening response, or CAR, Adam et al, 2006; Doane and Adam, 2010, but see Sladek and Doane, 2015), while trait loneliness was associated with a flatter decline in diurnal cortisol in late adolescence (Doane and Adam, 2010, but see, Sladek and Doane, 2015), for a null association between trait loneliness and cortisol slope in the same age group). Despite the insights provided by those data, critical gaps remain unaddressed in this literature.…”
supporting
confidence: 54%
“…For example, Doane and Adam (Doane and Adam, 2010) found that chronic loneliness was associated with a flatter diurnal cortisol slope in sample of 108 mostly female older adolescents, while the same association was not found by Sladek and Doane in a smaller, but demographically comparable, sample (Sladek and Doane, 2015). In our study, although trait loneliness was not associated with a flattened cortisol circadian rhythm, we found that children reporting high levels of daily loneliness—averaged across the three testing days—had a flatter cortisol slope.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The study by Jarrin et al (2015) also focuses on obesity and found sympathovagal imbalance to mediate the association between poor sleep (and later sleep timing and sleep-disordered breathing in particular) and obesity indices in a sample of 564 young adolescents (ages 10-12 years) atrisk obesity. Shifting gears to the CAR, Sladek and Doane (2015) used daily sleep diaries and actigraphy in college students to examine the interrelations of sleep, loneliness, and the HPA axis. The authors found that feeling more socially connected was associated with more time spent in bed and more time asleep for college students high in trait loneliness but associated with a longer sleep onset latency for students low in trait loneliness.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 99%
“…These studies underscore the value and importance of including biological measures in studies examining adolescents' sleep patterns and functioning. In addition, although not focused on physical and physiological characteristics, the Tavernier and Willoughby (2015) study in this issue complements the Sladek and Doane (2015) study by examining the bidirectional associations between sleep problems and social connectedness. In a 3-year longitudinal study of 942 university students Tavernier and Willoughby (2015) found that sleep quality was prospectively associated with more positive social ties and that this association was mediated by emotion regulation.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 99%